2017
DOI: 10.1016/s2215-0366(16)30375-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of serum neuronal cell surface antibodies in first-episode psychosis: a case-control study

Abstract: Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
151
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 33 publications
10
151
1
4
Order By: Relevance
“…The frequency of antibody positivity was around 5% or less in all but one study [13] and was less than 1% in two studies [11, 12]. Of the studies that produced positive results, five included a healthy control group for comparison [10-13, 15], and two of these studies, in addition to further testing in one of them, also identified antibodies in 0.4–1.2% of healthy controls [11, 12, 30], making interpretation of the results difficult. No group differences in seroprevalence were found, where reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of antibody positivity was around 5% or less in all but one study [13] and was less than 1% in two studies [11, 12]. Of the studies that produced positive results, five included a healthy control group for comparison [10-13, 15], and two of these studies, in addition to further testing in one of them, also identified antibodies in 0.4–1.2% of healthy controls [11, 12, 30], making interpretation of the results difficult. No group differences in seroprevalence were found, where reported.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven positive studies, four used a commercially available fixed cell-based assay (CBA) [10-12, 16], two used a live CBA [13, 15], and one used both, as well as a single molecule-based imaging method, for the sake of comparing approaches [14]. The majority of negative studies also used the same aforementioned commercially available CBA (or a modification of it) [17-22, 24-29], and four of these studies also included immunohistochemistry for further testing [19, 26-28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of the study patients with organic presentations were excluded which may be one reason for the low proportion of positive results in comparison with Lennox et al 2017(Lennox et al, 2017. Further, as the proportion of cases and of controls with antibody positivity was small, it remains a possibility that the negative findings may be due to insufficient statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is growing evidence that common psychiatric illnesses such a schizophrenia may be driven by an underlying antibody-mediated encephalitis, further softening the boundary between psychiatry and neurology. 10 In their case study Newrick et al 11 discuss the 'patient with psychotic depression languishing on a neurology ward for want of reasonably dosed antipsychotics'. Our patient reminds us of the 'encephalitic patient languishing on a psychiatric unit for want of i m m u n o s u p p r e s s i o n ' .…”
Section: Discussionmentioning
confidence: 99%